A CAF-1 dependent pool of HP1 during heterochromatin duplication - Quivy, Jean-Pierre (2004)
To investigate how the complex organization of heterochromatin is reproduced at each replication cycle, we examined the fate of HP1-rich pericentric domains in mouse cells. We find that replication occurs mainly at the surface of these domains where both PCNA and chromatin assembly factor 1 (CAF-1) are located. Pulse–chase experiments combined with high-resolution analysis and 3D modeling show that within 90 min newly replicated DNA become internalized inside the domain. Remarkably, during this time period, a specific subset of HP1 molecules (α and γ) coinciding with CAF-1 and replicative sites is resistant to RNase treatment. Furthermore, these replication-associated HP1 molecules are detected in Suv39 knockout cells, which otherwise lack stable HP1 staining at pericentric heterochromatin. This replicative pool of HP1 molecules disappears completely following p150CAF-1 siRNA treatment. We conclude that during replication, the interaction of HP1 with p150CAF-1 is essential to promote delivery of HP1 molecules to heterochromatic sites, where they are subsequently retained by further interactions with methylated H3-K9 and RNA.